Intermittent infusion of 0.25% bupivacaine through an intrapleural catheter for post-thoracotomy pain relief - Tetik, Ö; Islamoglu, F; Ayan, E; Duran, M; Buket, S; Çekirdekçi, A (Elsevier Science Inc, 2004)
Background. The present study was designed to evaluate the effectiveness of intrapleural 0.25% bupivacaine delivered by intermittent infusions for post-thoracotomy pain relief. Methods. Forty patients undergoing elective lobectomy were randomly, but equally, placed into two groups. An intrapleural catheter was inserted under direct vision during surgery. Group I received intrapleural 40 mL of 0.25% bupivacaine, group II was administered 40 mL of saline solution as a control group. Diclofenac sodium was administered as an additional analgesic, if required. Postoperative pain was evaluated using a visual analog scale (VAS), and Prince Henry pain scale. Arterial oxygen saturation, heart rate, and systemic arterial pressures were monitored. All observations were recorded 5,10,15, 20, 25, and 30 minutes after the injection, and thereafter at hourly intervals through the postoperative 24 hours. Results. The mean analgesia times were 5 hours and 2 hours in group I and group II, respectively. Therefore, bupivacaine administrations were repeated every 6 hours in group I, and saline with additional analgesic were administered every 4 hours in group II. The heart rate and arterial pressures did not show a significant difference. While the additional analgesic requirement was 180+/-10 mg/d in group II, there was no need for additional analgesic administration in the group I patients. Arterial oxygen was significantly higher in group I than in group II. Arterial carbon dioxide tension of group H was significantly higher than that of group I. While the postoperative atelectasis and pneumonia developed in four patients and one, respectively, in group II, no such complication was observed in group I. Conclusions. The easy placement of an intrapleural catheter and better pain relief observed in the present study suggest that intermittent pleural infusion of 0.25% bupivacaine has proven to be a safe and effective method for relief of post-thoracotomy pain.
Keywords: Postoperative Analgesia; Epidural Analgesia; Thoracotomy; Morphine; Anesthesia; Efficacy